Interaction with Search Engine through Keywords - Digital Marketing - Sethi, Nishu; Bhateja, Neha (International Journal of Psychosocial Rehabilitation, 2020)
The impact of digital marketing correspondence on item classes like books, music, design extras, attire, banking, web-based gaming, and so on has been very much explored by the scientists. In this paper we will describe how to search with keywords and refinement in the keywords for better searching on the Internet.